BASEMENT KOMPLEK BAYAH, KABUPATEN LEBAK, PROPINSI BANTEN - Patonah, Aton; Helmi, Faisal; Prakoso, Jodi; Widiaputra, Taufiq (Bulletin of Scientific Contribution, 2015)
Researching metamorphic rocks in Bayah and in its surrounding area has slight data so it has not been clear yet how the stratigraphic position, the age and the metamorphic rocks characteristic is in the study area. By using geological mapping and petrographic method, it showed that the metamorphic rock is believed to be the basement of Bayah complex which accreted because of reverse fault in the northwest so that the rock appeared together with the relatively younger rocks in the south (Bayah Formation and Granodiorite Cihara). These rocks showed that there are foliation, boudinage and crenulation structure consisting of various types of metamorphic rocks which are different in degrees of metamorphism (low grade – high grade metamorphism) and in protoliths as well, so these interpret as a result of orogenic processes of intermediate pressure metamorphism.